Corrugated cooling unit for accelerated cooling of rebar subjected to Tempcore process. (25th February 2020) - Park, Chun Su; Bae, Seh Wook; Cho, Jin Rae; Lee, Habeom; Kim, Yangjin; Moon, Young Hoon
Graphical abstract: Highlights: The turbulence induced by the corrugated cooler increases the cooling capacity. Heat transfer coefficient for convective and nucleate boiling is numerically obtained. RPI boiling model and realizable k-epsilon model are extended to the Tempcore process. 6.54% increase in the martensite volume fraction is achieved by the corrugated cooler. Abstract: An advanced cooling unit was developed and characterized to accelerate the cooling of steel rebars during the Tempcore process. Compared to conventional flat-surfaced coolers, the newly developed cooling unit uses a corrugated surface to generate turbulence. To estimate the cooling performance of the corrugated cooler, the heat transfer coefficient during the Tempcore process was obtained using a finite-volume method. The turbulence induced by the corrugated cooler reduces the vapor volume fractions and increases the heat transfer coefficient by up to 10%. The obtained heat transfer coefficient for convective and nucleate boiling was then applied in the model to predict the volume of martensite formed in the outer layer of the bar after the Tempcore process. The corrugated cooling unit was assembled and incorporated into an experimental simulator to evaluate its ability to accelerate cooling of rebars. For rebars treated in the corrugated cooler, a 6.54% increase in the martensite volume fraction with a 13 °C decrease in the self-tempering temperature was achieved. This result confirms that the developed corrugated cooler can be a reasonable alternative to increase cooling efficiency of Tempcore facility without upgrading the capacity of the water supplying system.